Clockers - Lee, Spike; Price, Richard, 1949-; Phifer, Mekhi; Washington, Isaiah; David, Keith; Blanchard, Terence; Hornsby, Bruce; Universal Pictures (Firm); Forty Acres & a Mule Filmworks; Child Hoods Productions; Universal Studios Home Video (Firm) (Universal City, CA : Universal Home Video, 1999)
A young drug dealer is hounded by the police to confess after his brother, a straight arrow, is arrested for murder.
Based on a novel by Richard Price.
Originally released as a motion picture in 1995.
Director of photography, Malik Hassan Sayeed; production design, Andrew McAlpine; editor, Sam Pollard; music, Terence Blanchard, Bruce Hornsby.
Mekhi Phifer, Isaiah Washington, Keith David, Pee Wee Love, Regina Taylor, Harvey Keitel, John Turturro.
MPAA rating: R.
DVD, Dolby digital stereo surround.
Keywords: Price, Richard, -- 1949- -- Film and video adaptations; Drug traffic -- Drama; African Americans -- New York (State) -- New York -- Drama; Detective and mystery films; Police films; Video recordings for the hearing impaired; Based on the book; Feature films; Detective films; Mystery films